Developing the Theater of Leadership: An Exploration of Practice and the Need for Research. (August 2015) - Tawadros, Tammy
The Problem: Recent models of leadership emphasize the importance of adaptive, strategic, and socio-emotional capabilities for success. The development of leadership has transformed from teaching about the concept to an experiential learning of leadership, an approach that focuses on identity and problem solving. Over the past decade, improvisational theater and interactive drama based leadership development has received increasing attention; moreover, many advocate its use as a powerful and innovative experiential learning tool, to foster self-awareness and increase ability to deal with the unexpected and unpredictable. Through simulated, unscripted scenarios with actors, improvisation allows experimentation, discovery, and rehearsal of leadership behavior in a group context. It generates individual, relational learning that is immediate, emergent, and relevant to the emotional and cognitive complexities of real-world leadership. There is a paucity of literature on theater-based leadership. This makes it difficult for HRD professionals to justify giving theater-based leadership development (TBLD) techniques preference over other, less resource-intensive techniques. The Solution: This article proposes a practical model for the systematic evaluation of TBLD techniques . A pathway mapping approach will be used. The model draws on recent social psychology research on social interaction and identity. Based on this, "micro" analytic techniques of discursive psychology and conversation analysis are proposed to examine patterns of leadership interaction behavior. The findings are to be used as a basis for building a "high fidelity, " evidence-based methodology for role-play and improvisation as development training for leaders. The approach offers a clear framework for HRD professionals. It will be used to analyze and inform the effective use of TBLD. This article is purely theoretical; it does not include empirical research. The Stakeholders: Many can potentially benefit by using TBLD techniques, including human resource (HR) professionals and HRD practitioners, leadership development specialists and training providers, organization development practitioners, and professional actor trainers.